Protective effect of astrocyte-conditioned medium on neurons following hypoxia and mechanical injury - YAN Ji-wen; TAN Tong-yan; HUANG Qi-lin (Chinese Journal of Traumatology, 2013)
【Abstract】Objective: To investigate the protec-tive effect of mouse astrocyte-conditioned medium (ACM) on hypoxic and mechanically injured neurons by a cell model in vitro, and to explore the possible mechanism. Methods: The model of hypoxic neuronal injury was caused by 3% O 2 in three-gas incubator. Neurons were cul-tured with ordinary medium or 20% ACM respectively and randomly divided into hypoxic group (hypoxia for 4, 8, 24 h and marked as H4R0, H8R0, H24R0) and hypoxia reoxygenation group (H4R24, H8R24, H24R24). Mechanical injury model was developed by scratching neurons cultured in 20% ACM or ordinary medium to different degrees. Neu-rons in both medium were divided into normal control group, mild, moderate and severe injury groups. The 20% ACM was added 24 h before hypoxia/reoxygenation or mechanical injury. The morphology and survival of neurons were observed and counted by trypan blue staining. The concentration of NO, lactic dehydrogenase (LDH) and membrane ATPase activity were detected by corresponding kits. Results: It was showed that 20% ACM can obviously promote the survival rate of hypoxia/reoxygenated neurons and scratched neurons as well. The morphology and num-ber of neurons exposed to hypoxia or scratch injury showed great difference between groups with or without ACM treatment. Compared with control group, the concentration of NO and LDH was much lower in hypoxic/reoxygenated neurons treated with 20% ACM, and the ATPase activity was higher. For the mechanical injury model, neurons with moderate injury also revealed a lower NO and LDH concen-tration than the control group. All the differences were sta-tistically significant (P<0.05). Conclusion: ACM can promote the survival and func-tional recovery of neurons following hypoxia or scratching to a certain degree. The mechanism may be associated with reducing the synthesis and release of NO and LDH as well as increasing the activity of membrane ATPase. Key words: Glial cell line-derived neurotrophic factor; Neurons; Cell hypoxia